ANALISIS PEMUNGUTAN RETRIBUSI PASAR GUNA MENINGKATKAN EFEKTIFITAS PENDAPATAN DAERAH KABUPATEN PAMEKASAN - Ria Rachmawati (Al-Amien Prenduan for Islamic Institute, 2021)
The purpose of this study was to analyze the activities of collecting market levies in order to increase the effectiveness of those applied to the Pamekasan Regency Industry and Trade Office and Regional Regulation No. 13 of 2012 concerning Market Levies. This type of research uses descriptive quantitative. This type of data uses quantitative data. The data source uses secondary data. The data collection technique uses documentation techniques in the form of local revenue reports and the stages of data analysis used by identifying market retribution collection activities, effectiveness analysis, growth analysis and trend analysis. The results showed that the activity of collecting retribution at the Department of Industry and Trade of Pamekasan Regency was in accordance with the Regional Decree of Pamekasan Regency Number 13 of 2012 concerning Market Retribution, so that the researchers considered that the activities of collecting Market Retribution at the Department of Industry and Trade of Pamekasan Regency had been effective. Based on the calculation of the effectiveness analysis of the industrial office, it has been effective. The growth of market retribution revenue has decreased significantly every year. Meanwhile, the average percentage growth for 3 years shows that every year the Department of Industry and Trade has not been maximized for collecting market levies so that the growth rate has not been met.